(untitled) (Conference on English Language Teaching, 2023)
This research investigated the effectiveness of quartet card games on student speaking ability. This research investigated whether teaching speaking using quartet card game can improve students speaking ability. This research used one group pre-test and post-test design and quantitative research method. The instrument used in this research was tests (pre-test and post-test). This research involves 70 students as a sample among eighth grade of SMP Attaufiqiyyah as a population. The research finding showed that from the calculation "to" is higher than the t table both at significance levels 5% and 1%. Significance 5% t table = 1,66 and t observation = 8,19, while significance 1% t table = 2,38 and t observation =8,19. In addition, the result of this study showed that the students are more motivated in learning English, especially in speaking subjects. Based on the result above, it can be concluded that quartet card games can improve students speaking ability. The result of this research shows that students who use quartet card games achieve better performance in improving students speaking ability than those who do not use quartet cards game.